Effects of phase transformation with respect to the orientation and velocity in the traction-deformed copper nanowire - Vega Guillén, Víctor Augusto (2020)
NCs have many unique behaviors that are not seen in volume level materials. The objective of the study is to know the effects of the transformation of phases with respect to the orientation and speed in the copper nanowire deformed by traction. Due to the need to better understand the deformation mechanisms through simulations and the molecular dynamics method with the potentials of the EAM type, we evaluate the phase transformation in the direct correlation between the stress-strain curve, and the percentage of the abundance of pairs. In the elastic region in a range of 60% to 80% of atoms they are forming FCC structures, about 10% to 20% the HCp structure, the formation of the BCC structure is minimal and the percentage of other formations are in a range of 20% to 40%, affected by speed and orientation as a result, the greatest modulus of elasticity is 100 GPa and yield strength of 9.0 GPa with an orientation of (111) this unique phenomenon allows the design of nanosystems.